Reframing the Issue: Child Care Advocacy in Alberta - Pasolli, Kelly (Atlantis)

(untitled) (Mount Saint Vincent University, 2013)
This article focuses on the organization, strategies, and motivations of the contemporary child care movement in Alberta. The concept of framing is used to explore the ways in which child care advocates negotiate the gap between their desires for policy change and their knowledge of what advances are feasible given the political realities of the province. In particular, the article emphasizes advocates’ use of gender-neutral, child-centred frames that focus on the developmental and economic benefits of child care, rather than feminist-informed frames that emphasize the need for public, universal child care. This has implications for the scope of policy reforms on the political agenda and for women’s equality in Alberta.